Unsteady CFD simulation on ash particle deposition and removal characteristics in tube banks: Focusing on particle diameter, flow velocity, and temperature. Issue 4 (August 2020) - Mu, Lin; Wang, Shuaitan; Zhai, Zhende; Shang, Yan; Zhao, Chen; Zhao, Liang; Yin, Hongchao
Abstract: This study establishes a numerical deposition and removal model coupled with unsteady gas–solid turbulent flow to predict transport, impaction, sticking, and removal (or rebounding) characteristics of ash particles with high alkali metals based on Ansys Fluent software extended by user–defined functions. Dynamic mesh analytical strategy is employed to adjust the grid on the interface of flue gas and deposition layer to illustrate ash deposit growth characteristics. In this study, the effects of particle size, flow velocity, and inlet gas temperature on formation and distribution of ash deposits are studied. The results indicate that ash deposit distribution has significant particle size dependence. Larger particles tend to deposit on the windward side of first–row tubes, and account for the greatest share of total deposited mass. Smaller particles may deposit on the leeward side of the tube surfaces. Variation in impaction rates with time are influenced by the thermophoretic force and enlarged deposition area. With the increase in flow velocity, total deposited mass increases gradually. The influence of flow temperature on impacting rates is mainly embodied in the effect of flow temperature on thermophoretic force. However, the increase in inlet gas temperature has little effect on the sticking efficiency and ash deposit distribution. Nevertheless, the total deposited mass shows an increasing trend with inlet flue gas temperature. Highlights: A numerical deposition (sticking/rebounding) model coupled with unsteady gas–solid turbulent flow was developed. Transport, impaction, sticking and removal characteristics of ash particles with high AAEM content were simulated. Dynamic mesh analytical strategy was employed to illustrate the ash deposits growth characteristics. Three important operational parameters including ash particle size, inlet flow velocity and gas temperature are selected.